Wholesale Prices in the United States, 1866-91 - Snider, Joseph L. (The Review of Economics and Statistics, 1924)
of the Aldrich Report do not extend beyond that year, but also by the fact that beginning with I890, and later, quarterly or monthly indexes of wholesale prices have been published by various agencies.2 In studying commodity prices over a period of years it is usual to construct index numbers: a comprehensive summary figure is obtained by averaging all of the individual series selected, by years, quarters, or months, and sub-indexes are often constructed by averaging the series by economic categories, such as farm 'products, textiles, metals, etc., or raw materials and manufactured goods, or producers' and consumers' goods. The comprehensive index is designed to show changes in the general price level, and the sub-indexes reflect the average price movements of related commodities. In this study the nature of the data made it necessary to proceed on the basis of quarterly rather than monthly quotations. A comprehensive or general price index and also group indexes were constructed, but in the latter a distinct de-